Undergraduate Medical Students’ Perception of Academic Environment in Bangladesh: A Gender-Wise and Phase-Wise Evaluation - Bhattacharjee, Sharmista; Permita Chakraborty, Pragwa; Nasim Uddin Chowdhury, Mohammed (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Medical education has undergone significant reforms globally with an aimto produce competent doctors. The evaluation of academic environments is crucial in maintaining quality of medical education. Students' perceptions of academic environments are crucial as they influence behavior and success. This study aims to assess gender-wise and phase-wise variations in undergraduate medical students' perceptions of academic environments in Bangladesh which may provide insights for improvement. Materials and methods: This cross-sectional study involved 400 students (Phase 1 to phase 4) from four medical colleges in Bangladesh, selected through random sampling.The Dundee Ready Education Environment Measure (DREEM) questionnaire was used to collect data. The genders and phases were compared by independent t-test and ANOVA, respectively, with the aid of SPSS. Results: Both gender-wise and phase-wise analysis showed a positive perception of overall environment and individual domains. Female students rated SPL (p=0.01), SPT (p.0.00), SPA (p=0.03) and DREEM (p=0.00) significantly higher than males. Phase 1 and 4 showed significant differences in SPL (p=0.01) and DREEM (p=0.04) while phase 2 and 4 revealed significances in SPT (p=0.04), SASP (p=0.01), SPA (p=0.03) and DREEM (p=0.01). Conclusion: Findings from this study may provide guideline to curriculum planners and administrators of the medical colleges for further improvement of academic environment. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 39-44